2014
DOI: 10.1186/1475-2875-13-416
|View full text |Cite
|
Sign up to set email alerts
|

Cost of treating inpatient falciparum malaria on the Thai-Myanmar border

Abstract: BackgroundDespite demonstrated benefits and World Health Organization (WHO) endorsement, parenteral artesunate is the recommended treatment for patients with severe Plasmodium falciparum malaria in only one fifth of endemic countries. One possible reason for this slow uptake is that a treatment course of parenteral artesunate is costlier than quinine and might, therefore, pose a substantial economic burden to health care systems. This analysis presents a detailed account of the resources used in treating falci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The estimated costs of treating a patient with severe malaria in this study are similar to those calculated in previous studies [ 15 , 16 ], although lower than those reported by Kyaw et al , which used a more detailed cost analysis approach [ 17 ]. The costs were highly variable, depending on the level and type of facility (public, private or missionary).…”
Section: Discussionsupporting
confidence: 81%
“…The estimated costs of treating a patient with severe malaria in this study are similar to those calculated in previous studies [ 15 , 16 ], although lower than those reported by Kyaw et al , which used a more detailed cost analysis approach [ 17 ]. The costs were highly variable, depending on the level and type of facility (public, private or missionary).…”
Section: Discussionsupporting
confidence: 81%
“…It would be expected that in areas with high malaria burdens, the per inpatient cost would be lower as fixed costs are spread over a larger number of patients. Meanwhile, another evidence showed that the cost for hospitalization services in China was much higher than that in Thailand [ 28 ]. Besides, the hospitalization cost was almost twofold compared to that in a recent study in China (2587 RMB, which adjusted and converted to 409.14 USD according to the value of money in 2011) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of information was directly obtained from the first page of medical records. Referring to one similar study [ 28 ], the direct medical cost in this study was classified into six categories: (1) Medications: including western medications and traditional Chinese medications, such as antibiotics and supportive treatment medications. Notably, anti-malarials were excluded from this category since they are free-of-charge and publicly available.…”
Section: Methodsmentioning
confidence: 99%
“…Cost-effectiveness was analyzed in 5 studies. 88,89,92,95,96 Most studies were published after 2010 76,78,[80][81][82][83][84][85][86][87][88][89][90]94,96 and concerned uncomplicated malaria only, 78,80,[82][83][84]88,89,[91][92][93]95,96 both uncomplicated and severe malaria, 76,79,81,86,90,94 with severe or moderate anemia 81 or severe malaria only 77,85,87 in all ages, 78,80,82,83,89,91,93 infants/ children, 76,80,…”
Section: Treatmentmentioning
confidence: 99%